2003
DOI: 10.1159/000069731
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events, Social Support, Attachment Security and Alexithymia in Vitiligo

Abstract: Background: It has often been suggested that stress might trigger vitiligo. However, only one study supported this hypothesis, and no study explored the role of other personality or social factors. Methods: Out-patients experiencing a recent onset or exacerbation of vitiligo (n = 31) were compared with out-patients with skin conditions in which psychosomatic factors are commonly were regarded as negligible (n = 116). Stressful events during the last 12 months were assessed with Paykel’s Interview for Recent Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 49 publications
7
75
0
3
Order By: Relevance
“…There was no difference with men or the vitiligo cohort as a whole. These results were concordant with respect to those of Picardi et al (Picardi et al, 2003). They also found no differences between vitiligo patients and controls regarding the total number of stressful events or the number of undesirable, uncontrollable, or major events.…”
Section: Stress Involvementsupporting
confidence: 91%
See 2 more Smart Citations
“…There was no difference with men or the vitiligo cohort as a whole. These results were concordant with respect to those of Picardi et al (Picardi et al, 2003). They also found no differences between vitiligo patients and controls regarding the total number of stressful events or the number of undesirable, uncontrollable, or major events.…”
Section: Stress Involvementsupporting
confidence: 91%
“…In Agarwal's study (Agarwal, 1998), half of the patients with vitiligo reported stressful events before disease onset. Meanwhile, other reports (Picardi et al, 2003) found no differences between vitiligo patients and controls when comparing numbers of stressful events. In our previous study, we found significant differences in the mean number of stressful events only between women with vitiligo and controls.…”
Section: Stress Involvementmentioning
confidence: 81%
See 1 more Smart Citation
“…It is widely believed that psychological stress, some personality traits, and psychiatric disorder complications are related to, and manifest as skin disease 13 . Thus, in the current study, the SCL-90-R was used to investigate common psychiatric symptoms in SD patients.…”
Section: Discussionmentioning
confidence: 99%
“…NSV is commonly precipitated by stress. This view has been recently challenged in a case-control study; however, a reduced ability to cope with stress may contribute to the clinical findings (38). There is a marked increase of calcitonin gene related peptide (CGRP) positive nerve fibers in involved skin (39).…”
Section: Melanocyte Destructionmentioning
confidence: 99%